2002
DOI: 10.1161/01.cir.0000032912.33237.bc
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance at Rest and During Exercise After Aortic Valve Replacement: Comparison of Pulmonary Autografts Versus Aortic Homografts

Abstract: Background The Ross procedure and aortic homografts have both been shown to have superior hemodynamic performance after valve replacement, but there have been few comparisons. Methods Sequential Doppler echocardiograms were performed up to 5 years after aortic valve replacement in 132 patients with the Ross procedure and 111 patients with an aortic homograft (AH). Measurements included assessment of valvular regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although allogenic and autologous substitutes recorded similar hemodynamic performance with mean and peak transaortic gradients <10 mm Hg in the vast majority of individuals [ 97 ], pulmonary autografts revealed minimal calcification or degeneration, whereas many individuals develop high transaortic gradients following bioprosthesis or homograft implantation [ 103 , 104 , 105 , 106 , 107 ]. This implies that the transvalvular gradient remains stable over time with the use of the PAs as reported in long-term follow-ups, whereas it tends to increase after the implantation of homograft or bioprosthetic conduits [ 48 , 108 , 109 , 110 , 111 ]. The presence of low transvalvular gradients is even more significant when we consider the population of young individuals who want to exercise after AVR surgery.…”
Section: Resultsmentioning
confidence: 90%
“…Although allogenic and autologous substitutes recorded similar hemodynamic performance with mean and peak transaortic gradients <10 mm Hg in the vast majority of individuals [ 97 ], pulmonary autografts revealed minimal calcification or degeneration, whereas many individuals develop high transaortic gradients following bioprosthesis or homograft implantation [ 103 , 104 , 105 , 106 , 107 ]. This implies that the transvalvular gradient remains stable over time with the use of the PAs as reported in long-term follow-ups, whereas it tends to increase after the implantation of homograft or bioprosthetic conduits [ 48 , 108 , 109 , 110 , 111 ]. The presence of low transvalvular gradients is even more significant when we consider the population of young individuals who want to exercise after AVR surgery.…”
Section: Resultsmentioning
confidence: 90%
“…One study demonstrated autografts have reduced LVOT peak velocities after valve replacement and reduced left ventricular wall thickness, which was not seen in a comparison to patients who receiving aortic homografts [37][38][39]. Beyond these benefits, the Ross procedure is typically used in physically active young adults, and the reason for this is due to the pulmonary autograft's ability to adapt to aerobic exercise without increasing the neo-aortic valve gradient, thus mimicking normal aortic physiology [40,41].…”
Section: Cardiac Remodeling After the Ross Proceduresmentioning
confidence: 99%
“…Ross procedure was also associated with a lower mean aortic gradient at follow-up after 13 years in a randomized controlled trial when compared to aortic homograft (5 mmHg versus 30 mmHg) [ 30 ]. Pulmonary autograft has been shown in several studies to mirror the native healthy aortic valve in hemodynamic performance during activity by maintain a low gradient with maximal exercise [ 44 , 45 , 46 ]. Newer bioprosthetic valves have modified designs that allow the placement of a larger valve, that sits in the supra-annular position, while avoiding a high aortic gradient and decreasing the incidence of patient-prosthesis mismatch [ 47 , 48 ].…”
Section: Hemodynamic Considerations For the Young Adultsmentioning
confidence: 99%